HIV-RELATED CEREBRAL TOXOPLASMOSIS TREATED WITH ANTIMALARIA MEDICINES: A CASE REPORT - Bintang, Andi Kurnia; Atiah, Ummu; Billi, Billi (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2024)
Background: Cerebral toxoplasmosis is a central nervous system disease caused by infection of intracellular parasite (Toxoplasma gondii) which happened due to activation of dormant form inside brain tissue in immunodeficient patients, especially in people living with HIV/AIDS (Human Immunodeficiency Virus/ Acquired Immunodeficiency Syndrome) or PLWHA. Case Presentation: A 36-year-old man with subacute headache, fever, changing personal behaviour and confusion that persisted for one month. He also had white spot in mouth, history of significant weight loss, meningeal signs, and motoric disturbance. His non contrast head CT scan shown presumptive cerebral toxoplasmosis appearance. We treated the patient with combined antimalaria drugs consists of Pyrimethamine-Sulfadoxin. Conclusion: Early diagnosis by available and rationale empiric treatment, then repeated cranial study is recommended which can dramatically reduce the high mortality and morbidity associated with this disease.